58.1k views
5 votes
For the graphed exponential equation, calculate the average rate of change from x = −4 to x = 4. Possible answer choices being; -1/3, -5/8, -4/5, -7/8

For the graphed exponential equation, calculate the average rate of change from x-example-1
User Inshallah
by
6.0k points

2 Answers

2 votes

Answer:

-5/8

Explanation:

User Tomer Mor
by
6.0k points
5 votes
the rate of change is given by:
[f(a)-f(b)]/[a-b]
thus the rate of change from x=-4 to x=4 will be:
[f(4)-f(-4)]/(4-(-4))
=[-5-0]/[4+4]
=-5/8

Answer: -5/8
User Mansur Ul Hasan
by
6.4k points